Students’ Perception of Learning English Through Hybrid Learning (Online and Offline) - Dewi Wahyuni; Arifuddin Arifuddin; Lalu Jaswadi Putera (AS-SABIQUN, 2022)
This research aims to: find out students’ perceptions of learning English through hybrid learning (online and offline), find out the difficulties of learning English through hybrid learning, and find out the positive impacts of learning English through hybrid learning according to high school students in Mataram. This research is a survey research that used quantitative descriptive method. 43 students of SMA Negeri 3 Mataram participated in this research. To collect data, questionnaires that consisted of close-ended questionnaire and open-ended questionnaire and interviews were used. The results of the study show that the positive impacts of learning English through hybrid learning are: (1) having a conducive classroom environment when learning English through hybrid learning, and (2) feeling comfortable since they can access the material anytime and anywhere. However, the students opined some difficulties in learning English through hybrid learning that included: (1) having difficulty in understanding the materials due to the unstable internet connection/signal, (2) having difficulty to express the ideas, and (3) having difficulty to participate in a more active, collaborative and communicative class discussion. The students’ perceptions toward the implemention of hybrid learning in learning English split into 3 categories: supportive, not supportive, and neutral perceptions. The total weight of each category in the questionnaires are “strongly agree” 8.7%, “agree” 25.1%, “neutral” 37.5%, “disagree” 20.1%, and “strongly disagree” 8.7%. The group of students that chose “neutral’ answers scores the biggest with 37.5% of the total students, followed by the groups of students that oppose or do not support the implementation of hybrid learning that comprises 33.8% or one third of the total students. The bottom position is seated by the group of students that propose or support the implementation of hybrid learning in learning English with 28.8% or less than one third of the total students. Thus, it can be concluded that the more students have neutral position towards the use of HL in learning English.